Parametric analysis for global single scattering albedo calculations. (1st August 2020) - Jeong, Jaein I.; Jo, Duseong S.; Park, Rokjin J.; Lee, Hyung-Min; Curci, Gabriele; Kim, Sang-Woo
Abstract: Single scatter albedo (SSA) is a key parameter in radiative transport models for estimating aerosol direct radiative forcing (DRF) and is also a major contributor to DRF uncertainty. We investigate the sensitivity of SSA calculations to physical input parameters (e.g., mixing state, size distribution, density, and refractive index of aerosols) associated with absorbing aerosols (e.g., black carbon [BC], brown carbon [BrC], and soil dust). We attempted to estimate global aerosol SSAs using the 3-D global chemical transport model (GEOS-Chem) and a post-processing tool of aerosol optical properties (FlexAOD) and evaluated the model by comparing it with observed values. The model reproduces the observed variability of both the surface aerosol concentrations and aerosol optical depth (AOD) obtained from the Surface Particulate Matter Network (SPARTAN), the global Aerosol Mass Spectrometer (AMS), and the Aerosol Robotic Network (AERONET). Our sensitivity tests show that the physical input parameters, which are not as well understood as aerosol mass concentrations, can lead to large uncertainties in global SSA values. We find that BC mixing state, BrC, and a dust size distribution have significant impacts on the global SSA calculation. Their combined use can reduce aerosol SSA bias in the model by 43% at 440 nm, compared to observations. We also find that the direct radiative effect (DRE) of global aerosols increases by 10% (from −2.62 W m −2 to −2.36 W m −2 ) when the SSA bias is corrected. Highlights: Single scattering albedo (SSA) has different characteristics at 440 and 870 nm. Black carbon density is an important factor in SSA estimation. Brown carbon absorption and dust size distribution reduce SSA at 440 nm. Mixing state and refractive index of aerosols affect SSA values. Correcting SSA bias increases aerosol direct radiative effect (DRE) by 10%.